TENAGA KONTRAK: MANFAAT DAN PERMASALAHANNYA - Maryono . (Jurnal Bisnis dan Ekonomi, 2009)
The global economic crisis has improved they competition between corporateinstitution. In the uncertenly condition every corporate has to make fast adaptation, sothe corporate has flexibility in business operation. One of the strategy is using contractworker (outsourcing) in order to rise flexibility. More over it will improve theperformance through human expenditure.This articles aim to explore the factors influences contract worker, benefit forworker, corporate, an economy, than to explore the problems and solutions.Key words : competition, contract worker, flexibility.